Cadmium-induced ER stress and inflammation are mediated through C/EBP–DDIT3 signaling in human bronchial epithelial cells - Kim, Jeeyoung (Exp Mol Med, 2017)
Cadmium (Cd), a major component of cigarette smoke, disrupts the normal functions of airway cells and can lead to the development of various pulmonary diseases such as chronic obstructive pulmonary disease (COPD). However, the molecular mechanisms involved in Cd-induced pulmonary diseases are poorly understood. Here, we identified a cluster of genes that are altered in response to Cd exposure in human bronchial epithelial cells (BEAS-2B) and demonstrated that Cd-induced ER stress and inflammation are mediated via CCAAT-enhancer-binding proteins (C/EBP)-DNA-damaged-inducible transcript 3 (DDIT3) signaling in BEAS-2B cells. Cd treatment led to marked upregulation and downregulation of genes associated with the cell cycle, apoptosis, oxidative stress and inflammation as well as various signal transduction pathways. Gene set enrichment analysis revealed that Cd treatment stimulated the C/EBP signaling pathway and induced transcriptional activation of its downstream target genes, including DDIT3. Suppression of DDIT3 expression using specific small interfering RNA effectively alleviated Cd-induced ER stress and inflammatory responses in both BEAS-2B and normal primary normal human bronchial epithelial cells. Taken together, these data suggest that C/EBP signaling may have a pivotal role in the early induction of ER stress and inflammatory responses by Cd exposure and could be a molecular target for Cd-induced pulmonary disease.